GEOTECHNICAL SOLUTIONS FOR ROAD STABILITY IN HILLY REGIONS AND THEIR COMMUNITY BENEFITS - Mohamad, Dadang (GoAcademica Research dan Publishing, 2024)
This study explores the implementation of geotechnical solutions to enhance road stability in hilly regions and examines the associated community benefits. Hilly areas present unique challenges such as landslides, erosion, and slope instability, which can compromise road infrastructure and safety. The research aims to identify effective geotechnical measures that can mitigate these issues and improve road stability. Utilizing a mixed-methods approach, the study combines quantitative data from field tests and engineering assessments with qualitative insights from local community interviews. The findings indicate that implementing techniques such as retaining walls, proper drainage systems, and soil reinforcement significantly enhances road stability. These improvements not only reduce the incidence of road failures and accidents but also contribute to the economic and social well-being of local communities. Improved road conditions facilitate better access to markets, healthcare, and education, thereby enhancing the quality of life for residents. The study provides valuable recommendations for policymakers and engineers to incorporate geotechnical solutions in road construction projects in hilly regions to ensure long-term stability and community benefits.